Penerapan Extreme Programming Dalam Perancangan Sistem Informasi Praktik Industri Berbasis Website - Ika Parma Dewi; Rizkayeni Marta; Daniel Rinaldi; Afif Rahman Riyanda; Yose Indarta (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The development of information technology makes all activities that used to run offline become online. The purpose of this study is to (1) Design and build a website-based Industrial Practice information system in the Information Technology Education Study Program, (2) Help students to find out information before or after Industrial Practice, (3) Assist admins in providing information, and lecturers in terms of assessment and guidance in the implementation of Industrial Practices. The development of this research uses the Extreme Programming method which has several stages, namely Requirements, Planning, Design, Coding, and Testing. The tests used in this study were internal testing, external testing and user acceptance test (UAT) testing. Internal testing uses browser testing and functionality testing, external testing uses blackbox testing and user acceptance test (UAT) testing uses iteration testing with the aim of testing the functionality of the menus in the application that are running well. The results of this study conclude that a website has been successfully built that can help study programs, both lecturers and students by 75%, (2) Assist study programs in managing student data in terms of registration of Industrial Practices and assessment of Industrial Practices, (3) The system can provide information related to the place of practice, practice scores, guidance information, and the overall average score of students who have done industrial practice.